APLIKASI KODA Sis (KOMBINASI DATA SISWA) DALAM KEGIATAN HIMPUNAN DATA BELAJAR SISWA - Nurdin, Astoni (JURNAL FOKUS KONSELING, 2017)
The research is based on the activity problem of guidence and counseling teachers in compiling the students learning data that currently it tends to be done manually. The research aims was to gain an overview of the effectiveness of the application of empirical KODA Sis (Combined Data of Students) in compiling the students learning data. The research used quantitative approach and pre-experiment in one group design. Sample consisted several junior high school teachers of guidance and counseling in district of Sukasari-Bandung in the academic year of 2013/2014 as the main respondent. Application of KODA Sis was developed from directive counseling approach as the basis of design concept. Stages of directive counseling approach was adopted as the name of the application features KODA Sis. The results showed that KODA Sis application is effective in improving the arrangement of student learning data set. Although KODA Sis applications have some limitations, but the innovative step of KODA Sis application is expected to be a basic model for further application development data set.